iVR-MANUALTHERAPY innovation educative project dataset. - Cuesta-Vargas, Antonio; Trinidad-Fernández, Manuel; Bossavit, Benoit; Fuentes-Abolafio, Iván José; García-Conejo, Celia; Mayorga-Vega, Daniel; Díaz-Balboa, Estíbaliz (Universidad de Malaga, 2025)
A Mixed-Methods Cluster Randomized Control Trial was performed in manual therapy students of University of Malaga with no prior experience in manual therapy. An iVR application for head-mounted displays was designed to teach a knee manual therapy technique. The Experimental group used the new iVR application during the traditional teaching method class, while the Control group received only the traditional method. User experience (Spanish version of Short Version of the User Experience Questionnaire and ad-hoc survey with three questions responsed based on a 5-point Likert scale), iVR experience only in the experimental group (Simulator Sickness Questionnaire and three open questions) and learning experience (specific ad-hoc rubric for the femorotibial mobilization technique) were collected quantitatively and qualitatively after the session.
Article not published yet: iVR-MANUALTHERAPY. New Learning Manual Therapy Technique Using An Immersive Virtual Reality Environment in Undergraduate Students: A Mixed-Methods Cluster Randomized Controlled Trial. Manuel Trinidad-Fernández; Benoît Bossavit; Ivan José Fuentes-Abolafio; Celia García-Conejo; Daniel Mayorga-Vega; Estíbaliz Díaz-Balboa; Antonio Cuesta-Vargas
Article not published yet: iVR-MANUALTHERAPY. New Learning Manual Therapy Technique Using An Immersive Virtual Reality Environment in Undergraduate Students: A Mixed-Methods Cluster Randomized Controlled Trial. Manuel Trinidad-Fernández; Benoît Bossavit; Ivan José Fuentes-Abolafio; Celia García-Conejo; Daniel Mayorga-Vega; Estíbaliz Díaz-Balboa; Antonio Cuesta-Vargas 2. Data processing methods Data collected from online surveys using the software Limesurvey (The LimeSurvey Project Team). The only data processing was performed using statistical software to present descriptive data and inferential analysis. 3. Software or instruments needed to interpret the data: The file is in CSV format so anyone can open it. We performed the qualitative analysis using Atlas.ti software, and the quantitative analysis using SPSS software.
Keywords: Fisioterapia; Realidad virtual; Enseñanza - Innovaciones; Manual therapy; Virtual reality